SOME FIXED-POINT RESULTS FOR ASYMPTOTICALLY REGULAR MAPS IN N-FUZZYb-METRIC SPACE (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
In this paper, we define N-fuzzy b-metric space and then weinvestigate fixedpoint results on the structure of N-fuzzy b-metric space using asymptotically regular map andasymptotically regular sequence. These theorems generalize and improve some known fixedpointtheorems in literature.